Trypanosoma cruzi, the Causal Agent of Chagas Disease: Boundaries between Wild and Domestic Cycles in Venezuela - Herrera, Leidi (Frontiers in Public Health, 2014)
American trypanosomiasis or Chagas disease, caused by Trypanosoma cruzi, occurs between triatomine vectors and mammals, including man. T. cruzi has 150 Ma in America with almost 10 million of infected people today. The overlapping of its wild and domestic ecotopes is increasing. The host-parasite imbrications has been discerned by the study of infection patterns, transmissibility and transmission cycles in natural and laboratory models, through to parasitological and molecular tests. This article describes specific parasite niches, as plant biocenosis or biological corridors between domestic and wild ecotopes and helps distinguish Chagas disease risks and the borderline between wild and domestic transmission cycles, with emphasis on Venezuelan studies.